Predictors of preterm birth in Western Ethiopia: A case control study - Regasa, Misganu Teshoma (PLoS One, 2021)
BACKGROUND: Early neonatal death caused by preterm birth contributes the most for perinatal death. The prevalence of preterm birth continues to rise and is a significant public health problem. The exact cause of preterm birth is yet unanswered, as mostly preterm birth happens spontaneously. Predictors of preterm birth in developing countries like Ethiopia were not well investigated, and no study was conducted before this in the study area. OBJECTIVES: To identify predictors of preterm birth in Western Ethiopia, 2017/2018. METHODS: Health facility-based unmatched case-control study was conducted from October 20/2017-march 20/2018 in 4 Hospitals. A total sample size of 358 women was recruited. From this 72 were cases and 286 were controls. Cases were mothers who gave Preterm birth, and controls were mothers who gave birth at term. Ethical clearance was obtained from Wollega University ethical review committee. A pre tested, structured questionnaire was used to collect data. Data entry and analysis was done using Epi Data 3.1 and SPSS version 21, respectively. Logistic regression was done to identify predictors of preterm birth. RESULT: Three hundred fifty-eight women participated in this study of which 72 were cases and 286 were controls; making the overall response rate of 100%. Lack of antenatal care visit [AOR = 3.18, 95% CI 1.37–7.38]),(Having 1–2 antenatal care visit [AOR = 2.27, 95% CI 1.18–4.35]),history of previous preterm)[AOR = 5.19, 95% CI1.29–20.88],Short Interpregnancy Interval [AOR = 4.41.95% CI 2.05–9.47],Having Reproductive tract infections [AOR = 2.54, 95% CI 1.02–6.32] and having Obstetric complications [AOR = 2.48,95% CI 1.31–4.71] were found to be predictors of preterm birth. CONCLUSION AND RECOMMENDATION: Risk factors of preterm delivery are multifactorial and depend on geographical and demographic features of the population studied. Hence results of studies from one area might not be applicable to another area. Antenatal care visits are unique opportunities for early diagnosis and treatment of problems. Therefore, antenatal care should be strengthened, and appropriate counseling should be given at each antenatal care follow up. Maintainning optimum birth interval through family planning, and early identification and treatment of reproductive tract infections are mandatory.